FREQUENCY AND DIAGNOSTIC FEATURES OF CRANIAL POLYNEUROPATHIES ASSOCIATED WITH COVID-19 (Web of Teachers: Inderscience Research, 2025)
Currently, 45% of patients who have recovered from COVID-19 face neurological disorders. These complications range from neurasthenia to severe conditions such as brain ischemia, encephalomyelitis, encephalopathy, and polyneuropathies (damage to the peripheral nervous system). Among these, cranial nerve lesions occupy a significant place and, according to international publications, are observed in patients at varying times after recovering from COVID-19. However, existing data remain insufficient for practical, theoretical, and statistical analysis, necessitating deeper study and increased attention to this issue.